Make a promise: the valuation adjustment mechanism in Chinese private target acquisitions - Bi, Xiaogang (Routledge, 2021)
The valuation adjustment mechanism (VAM) is a contingent-payment contractual arrangement used in the Chinese mergers and acquisitions (M&As) market. The ‘two-direction payment’ design of Chinese VAMs can reduce deal uncertainty and generate value, especially for poorly performing companies that can use VAM contracts to boost short-term performance. I find in this empirical investigation that acquirers applying VAM terms have significantly higher market returns after addressing endogeneity. I also document that poorly performing bidders sign larger VAM contracts, pay higher bid premiums and achieve higher operating performance, and which types of firms are more likely to adopt a VAM in transactions.